Prevalence of scoliosis in excessive weight bearing female market workers more than 50 years old and working more than 5 years in Pasar Kumbasari, Denpasar, Bali - Mugiillan Sathival; I Nyoman Mangku Karmaya; Yuliana . (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2018)
Market workers tend to work a lot in order to feed their family. A lot of human labour work is done at the expense of their health status in order to make a living. Aim: This study was conducted to determine the prevalence of scoliosis in female market workers in Pasar Kumbasari, Denpasar, Bali and the load lifting technique used to carry the loads in the market. Methods: This is a cross sectional descriptive study done with non-probability consecutive sampling. Questionnaires were distributed to aid in obtaining information regarding the study. Results: Of the total 115 female market workers interviewed, 7 of them had scoliosis. The scoliosis was apparent with abnormal gait associated with scoliosis and confirmation with the graphical aid used together with the questionnaires. As for the load lifting method used was carrying the loads over their heads. Many of the workers complained of pain in their neck and shoulders, arm and leg joints and lower back pain. The workers are found to be working in excess of 8 to 9 hours every day with rest in between periods when there are no people coming to buy things in the market. Conclusion: It can be concluded that the prevalence of scoliosis in female market workers in Pasar Kumbasari is 0.061. The load lifting technique commonly used is carrying the loads over their heads.